EFEKTIVITAS AROMATERAPI LAVENDER PADA PASIEN HIPERTENSI DI DESA PRIGI KECAMATAN PADAMARA KABUPATEN PURBALINGGA - Bahari, Egin Wahyu Septiawan; Ulfah, Maria (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Hypertension is a condition where the blood pressure in the arteries is too high. Hypertension occurs due to excessive workload of the heart when pumping blood throughout the body to meet the needs of oxygen and nutrients by the body. Hypertension is a leading cause of death that is often referred to as the silent killer disease. Hypertension, or high blood pressure, can cause pain, especially headaches and pain in the neck area, due to increased pressure on the blood vessel walls. Pain in hypertension can be treated with various alternatives, both pharmacologically and non-pharmacologically. Pharmacologically, it can be treated with analgesic drugs. One natural method that is considered effective in reducing pain is lavender aromatherapy. This case study aims to describe the application of Lavender Aromatherapy in Hypertension Patients in Prigi Village, Padamara District, Purbalingga Regency. The case study was carried out by observation for 2x meetings and the intervention of giving lavender aromatherapy for 2 days on December 11-12, 2024. The results of the case study of the application of lavender aromatherapy on the first day the patient was still in pain by showing a decrease in the pain scale on the second day. On the first day, the patient's level before being given lavender aromatherapy therapy with a pain scale of 5 (moderate pain) after being given lavender aromatherapy therapy became 4 (moderate), on the second day there was a significant decrease in the pain scale after being given lavender aromatherapy therapy, namely scale 2 (mild pain). Lavender aromatherapy in hypertension patients in Prigi Village, Padamara District, Purbalingga Regency is effective in reducing pain applied for 2x24 hours showing significant results from a pain scale of 5 (moderate pain) to a pain scale of 2 (mild pain).